Teologi Pembebasan: Gerakan Feminisme Kristen dan Pendekatan Dialog Martin Buber: Liberation Theology: The Christian Feminism Movement and Martin Buber's Dialogue Approach - Yahya Afandi (Sekolah Tinggi Teologi Satyabhakti, Malang)
It cannot be denied that the presence of feminist liberation movements and theology has left such a profound influence on the history of the paradigm shift of the church even more into the wider scope. The theology of feminism has also correctly demonstrated the general failure of men in fulfilling God's plan regarding the purpose of his creation, since love in a husband-wife life is described as Christ loves to His church. The next positive contribution of the theology of liberation of feminism has also stood against the practice of oppression, humiliation, manipulation and even the exploitation of women. It should be noted, however, that in addition to the great contributions that can even trigger a paradigm shift, feminist movements and theology also leave problematic traces. This Christian feminist flow moves in a Christian framework but their method of feminism and theology approach generally entirely uses a liberal perspective. On the one hand they assume that this developed theology comes from the inspired word of God, but on the other hand they step out of the orthodoxy of traditional Christian faith. One of the terms used to respond to feminist movements and theology is that they apply